Kazakhstan Reversing Productivity Stagnation : Country Economic Memorandum - World Bank (World Bank, Washington, DC, 2019)
After experiencing exceptional economic growth in the 2000s, Kazakhstan’s economy has slowed sharply since the global financial crisis, putting development achievements at risk. The economic slowdown has been caused by sharply lower commodity prices, and structural degradation of the economy. Kazakhstan’s productivity growth has steadily fallen over the past two decades. Falling within-sector productivity improvements are the driving force behind Kazakhstan’s productivity slowdown. The private sector is significantly constrained and does not exhibit many important features of healthy private sectors worldwide. Empirical evidence suggests that business entry rates are relatively low in Kazakhstan, even controlling for the structure of economy. The evidence shows that new (and small) firms are more productive than older (and larger) firms. The corrosive patterns must be corrected to revive productivity, which is essential for higher economic growth - since higher investment cannot substitute for productivity growth in the long run. The first policy imperative is to level the playing field for all firms - well-connected or otherwise. The second policy is to strengthen the rule of law and to deal more aggressively and comprehensively with corruption. Third, the governments will need to introduce structural changes in the economy to boost private investment and reduce a disproportionately large role of the state in the economy.